Implementation of the c-phi reduction procedure in Cast3M code for calculating the stability of retaining walls in the layered backfill with strength parameters reduction by elasto-plastic finite element analysis using fields data - Ambassa, Zoa; Amba, Jean Chills; Tamaskovics, Nandor (Comptes Rendus. Mécanique)
This paper presents an implementation of the c-phi reduction procedure in the finite element code Cast3M. This procedure is first validated on a simple example of bearing capacity of a strip footing and then used to evaluate the stability factor of a geotechnical structure composed of two levels of backfill retained by two retaining walls, with a road built on the top of the second backfill. The results of the c-phi reduction procedure for the construction of first and second backfill are also compared to other analysis methods classically used in geotechnics and to the results of finite element calculations.